Interaction between the oxidative balance score and serum per- and poly-fluoroalkyl substances (PFASs) on liver health: analysis of the NHANES 2007-2018 dataset - Ren Zhou; Fei Chen; Lei Zhang; Yu Sun; Hong Jiang; Rong Hu; Jia Yan (Komiyama Printing Co. Ltd, 2024)
Background: Per- and poly-fluoroalkyl substances (PFASs) are pervasive synthetic compounds, prompting investigations into their intricate interactions with lifestyle factors and health indicators because of their enduring environmental presence and bioaccumulation. This study aimed to explore the effects of the oxidative balance score (OBS) and PFAS on liver-related indices. Methods: Twenty dietary and lifestyle factors were used to calculate the OBS. The serum concentrations of PFASs were measured, and their sum was calculated for analysis. The levels of liver markers were also evaluated. Linear regression models and interaction analyses were used to assess the associations between OBS, PFAS concentrations, and liver indices. Results: The results revealed an inverse association between high OBS and perfluorooctane sulfonic acid concentration, as well as the sum of PFAS concentrations. OBS was positively associated with liver markers. The PFAS concentrations were positively associated with total bilirubin, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) levels. Interaction analyses revealed significant interactions between OBS and specific PFASs for alkaline phosphatase (interaction P < 0.05). Possible interactions were also found between OBS and specific PFASs for ALT, and AST levels (interaction P < 0.10). Conclusions: This study clarified the association between total PFAS and OBS. This association was significant mainly for diet-related OBS. PFAS and OBS are associated with liver-related indicators in the blood.